Pengaruh Kualitas Produk, Fear Of Missing Out (Fomo), Social Influence, Digital Marketing, Event Marketing Terhadap Keputusan Pembelian Jersey Sepak Bola Tim Nasional Indonesia (ERSPO) - Ivan Maulana; Endika Perdana (Journal of Economic and Business Advancement, 2026)
This study examines the causal relationships between product quality, fear of missing out (FOMO), social influence, digital marketing, and event marketing on purchasing decisions for the Indonesian National Team jersey produced by Erspo. Employing a quantitative explanatory design, data were collected from 238 respondents in the Jabodetabek area using purposive sampling and analyzed through SEM-PLS with SmartPLS 4.0. The findings reveal that product quality, FOMO, and social influence significantly and positively influence purchasing decisions, while digital marketing and event marketing demonstrate negative and non-significant effects. The model explains a moderate proportion of variance in purchasing decisions, indicating that consumer behavior is shaped by an interplay of symbolic, psychological, and social mechanisms. Social influence emerges as the most dominant factor, reflecting the role of collective identity and peer validation in shaping consumption patterns.